Використання технологій METAHUMAN у середовищі UNREAL ENGINE для створення реалістичних моделей людини - Єламков, Я. О.; Кулішова, Н. Є. (ХНУРЕ, 2025)
This paper describes metahuman technology created for the Unreal Engine game engine that creates realistic people for real-time animation.
Keywords: модель людини; Unreal Engine